Evaluating LFWD Testing for Characterizing Subgrade Layers Using Regression Analysis and Artificial Neural Network Model - H. Abdulkareem, Ahmed (Iraqi Journal of Civil Engineering, 2017)
The Light Falling Weight Deflectometer (LFWD) was developed to estimate the in-situ elastic modulus directly to the layers near the base as subgrade and subbase layers. The field tests were carried out on selected sections from landfill project within Anbar Province. Furthermore, Forty test sections have been constructed and tested at the Civil Engineering Department- University of Anbar. All sections were tested using the ZFG 3000 model - LFWD in companion with the Plate Load Test (PLT) which were used as reference measures. Regression analyzes were performed to determine the best correlation between the elastic modulus obtained from LFWD and PLT tests. ANN model was used to calculate Evd and compare the regression statistical model. It was found that the ANN model showed a higher performance than regression analysis in predicting Evd. Satisfactory correlations were obtained, which showed that LFWD could be a promising device for in-situ characterizing of subsurface and subgrade layers.